2018
DOI: 10.5582/irdr.2018.01007
|View full text |Cite
|
Sign up to set email alerts
|

Early electronic screen exposure and autistic-like symptoms

Abstract: Prevalence autism spectrum disorders (ASD) has been on rise, but many studies suggests over-diagnosed. Currently, children have more access to electronic media on the daily basis than those of previous generation. Some studies suggest that increases screen time is associated with melanopsin-expressing neurons and decreasing gamma-aminobutyric acid (GABA) neurotransmitter, and thus results aberrant behavior, decreased cognitive, and language development. Early exposure of electronic media in early life (< 2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…The younger the age and the longer the screen exposure time, the more serious the impact on language development. Hermawati reported that early exposure to electronic media in early life (an age < 2 years) had a negative impact on language ( 38 ). Chonchaiya et al found that children who started watching TV as early as 12 months and watched TV for more than 2 h a day were six times more likely to have language delays.…”
Section: Discussionmentioning
confidence: 99%
“…The younger the age and the longer the screen exposure time, the more serious the impact on language development. Hermawati reported that early exposure to electronic media in early life (an age < 2 years) had a negative impact on language ( 38 ). Chonchaiya et al found that children who started watching TV as early as 12 months and watched TV for more than 2 h a day were six times more likely to have language delays.…”
Section: Discussionmentioning
confidence: 99%
“…Screen time has adverse effects on both children with ASD and children with typical development. These adverse effects include poor academic performance (5), sleep problems (6), attention problems (7), social behavior deficits (8), obesity (9), adverse cardiovascular events (10), language delay (11), mood disorder (12), and even autistic-like symptoms (13).…”
Section: Introductionmentioning
confidence: 99%
“…In this model, excessive screen time in young children as an inappropriate environmental experience during critical periods of brain development and neuroplasticity leads to the specialization of brain non-social pathways and leads to the development of autism disorder (Heffler & Oestreicher, 2016). Hermawati et al (2018) demonstrated the relationship between early electronic screen exposure and autistic-like behaviors (e.g., language delay, short attention span and hyperactivity) in children (Hermawati, Rahmadi, Sumekar, & Winarni, 2018). Yurika et al (2018) found that excessive screen time in children was associated with autistic symptoms (i.e., ocular problems, hyperactivity and language delay).…”
Section: Introductionmentioning
confidence: 99%